Unemployment of disadvantaged groups in Czech Republic - Tišerová, Gabriela; Kadeřábková, Jaroslava, 1942-; Khendriche Trhlínová, Zuzana, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
The thesis deals with theme unemployment of disadvantaged groups. In theoretical part are clarified approaches to study and defined terms, which are used in thesis, asses the situation of labor market in Czech Republic. Then are defined disadvantaged groups, analyzed theirs disadvantages, problems and consequences to claim in the labor market. In practical part, author deals with support integration of disadvantaged groups; it deals with strategic documents of problems of unemployment from EU to town level. The thesis deals with the active labor market policy and social firm as a type of support integration disadvantaged groups to labor market. Object of thesis is finding, on the basis analyze, actual state of labor market and possibilities of integration disadvantaged groups in period of finances deficiency and with less possibilities of welfare state supports.
Vedoucí práce: Jaroslava Kadeřábková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: veřejná správa a regionální rozvoj [obor bakal. práce]; bakalářské práce; bachelor's theses